Reflection note: confessions of a Muslim researcher – considering identity in research. Issue 5 (2nd September 2020) - Islam, Maisha
ABSTRACT: This research note explores some of the contentions that have emerged from Muslim-on-Muslim research and how this can implicate the researcher more personally. Speaking in the context of methodological concerns arising from qualitative research, the paper consider the following aspects: inappropriate access of participants, over-representation of own experiences, and questioning fundamental parts of your identity. Whilst certain experiences can shake the foundations of being a researcher and even sense of self, these should ultimately be welcomed. It is concluded that, in taking the time to reconcile from such tensions emerging from our multiple identities, it can allow for becoming a more rigorous and reflexive researcher.